The effect of partial sleep deprivation on agility and vertical jump in basketball players - Ghasemabad, K. H.; Tengku-Kamalden, T. F. (Journal of Human Sport & Exercise, 2017)
The aim of this study was to examine the effects of partial sleep deprivation on two consecutive nights on agility and vertical jump of basketball players. Participants of this study were 30 healthy Iranian basketball players (male, Mage = 18.8 years (SD = ±1),) who had at least 5 years` experience in the secondary league of Iran, they were randomly assigned in partial sleep deprivation (PSD) (n= 15) and control group (n= 15). A pretest-posttest design was used in the present study. Two post-test was conducted after the first and second night of sleep deprivation. All the tests has been measured and recorded, and data were analyzed by SPSS version 22. Result of repeated measure ANOVA illustrate that, a significant difference between the scores of treatment group in the three times of measurements, while the results of control group were not significant between the pre-test, post-test 1 and post-test 2. Subjects in PSD groups had a significant changes (P ..05) in the first night of sleep deprivation and even more significant decrease (P ..05) in the second night of sleep deprivation, however, control group has no significant differences (P ..05) in their performance in all the measurement. In conclusion partial sleep deprivation has significant effects on agility and vertical jump of basketball player and this effects is more outstanding when it goes for two consecutive nights.